2015
DOI: 10.1038/srep11729
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of positive selection in East African Shorthorn Zebu: A genome-wide single nucleotide polymorphism analysis

Abstract: The small East African Shorthorn Zebu (EASZ) is the main indigenous cattle across East Africa. A recent genome wide SNP analysis revealed an ancient stable African taurine x Asian zebu admixture. Here, we assess the presence of candidate signatures of positive selection in their genome, with the aim to provide qualitative insights about the corresponding selective pressures. Four hundred and twenty-five EASZ and four reference populations (Holstein-Friesian, Jersey, N’Dama and Nellore) were analysed using 46,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 59 publications
7
87
1
Order By: Relevance
“…A previous study reported the positive selection of genomic regions associated with heat shock and heat stress response in East African Shorthorn Zebu cattle as an adaptation to perform under heat stress conditions (Bahbahani et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…A previous study reported the positive selection of genomic regions associated with heat shock and heat stress response in East African Shorthorn Zebu cattle as an adaptation to perform under heat stress conditions (Bahbahani et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…In accordance with our result, immune response genes, heat shock and heat stress response genes, and genes related to hair and skin structure have been reported to be under selection in African cattle in response to parasite infestation and high environmental temperature (Bahbahani et al . ; Makina et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that, following repeated annual exposure to migrating wildebeest, the African breed is more resistant to AlHV-1. This view is supported by recent genetic studies on the closely-related East African Shorthorn Zebu, which provide evidence of selection for traits related to survival in the African environment, including factors such as resistance to endemic pathogens (Bahbahani et al, 2015, Murray et al, 2013). Additionally the increased survival of SZC seen could be the result of natural adaptive immunity following previous exposure.…”
Section: Discussionmentioning
confidence: 87%